Prevalencia de hipertensión y prehipertensión en jóvenes - Ramos Torres, Jorge Alberto (Universidad y Salud, 2012)
Introduction: Many research projects suggest that essential hypertension can be present at an early age; this implies that blood pressure in young adults is a risk indicator for essential hypertension in adulthood. This study was aimed to standardize the blood pressure levels of young university students determining their relationship with the universal patterns and also to identify student’s habits and lifestyle, in order to establish the presence of risk factors for hypertension. Methods: Two hundred forty young students (ages ranging from 18 to 23) participated in this cross-sectional study. Their blood pressure was tested and a subsequent survey of prevalence was applied. The analysis of the information was carried out in Epi info and SPSS statistical packages and the participants signed a consent form. Results: The most relevant finding was the prevalence of prehypertension in a group of young participants, as well as the presence of stage I hypertension in some of them. It was also clear an exposure to cardiovascular risk factors among the participants. Conclusions: Changes in blood pressure and exposure to cardiovascular risk factors among the participants need to be further monitored and reevaluated.